Toward a Disease-Modifying Therapy of Alpha-Synucleinopathies: New Molecules and New Approaches Came into the Limelight - Mae Upcott; Kirill D. Chaprov; Vladimir L. Buchman (Molecules)
The accumulation of the various products of alpha-synuclein aggregation has been associated with the etiology and pathogenesis of several neurodegenerative conditions, including both familial and sporadic forms of Parkinson’s disease (PD) and dementia with Lewy bodies (DLB). It is now well established that the aggregation and spread of alpha-synuclein aggregation pathology activate numerous pathogenic mechanisms that contribute to neurodegeneration and, ultimately, to disease progression. Therefore, the development of a safe and effective disease-modifying therapy that limits or prevents the accumulation of the toxic intermediate products of alpha-synuclein aggregation and the spread of alpha-synuclein aggregation pathology could provide significant positive clinical outcomes in PD/DLB cohorts. It has been suggested that this goal can be achieved by reducing the intracellular and/or extracellular levels of monomeric and already aggregated alpha-synuclein. The principal aim of this review is to critically evaluate the potential of therapeutic strategies that target the post-transcriptional steps of alpha-synuclein production and immunotherapy-based approaches to alpha-synuclein degradation in PD/DLB patients. Strategies aimed at the downregulation of alpha-synuclein production are at an early preclinical stage of drug development and, although they have shown promise in animal models of alpha-synuclein aggregation, many limitations need to be resolved before in-human clinical trials can be seriously considered. In contrast, many strategies aimed at the degradation of alpha-synuclein using immunotherapeutic approaches are at a more advanced stage of development, with some in-human Phase II clinical trials currently in progress. Translational barriers for both strategies include the limitations of alpha-synuclein aggregation models, poor understanding of the therapeutic window for the alpha-synuclein knockdown, and variability in alpha-synuclein pathology across patient cohorts. Overcoming such barriers should be the main focus of further studies. However, it is already clear that these strategies do have the potential to achieve a disease-modifying effect in PD and DLB.